Prioritizing Citrus Nutrient Management Decisions - Thomas A. Obreza (EDIS)
This document is SL 199, a fact sheet of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First printed: January 2003.